Lives of the explorers : discoveries, disasters (and what the neighbors thought) - Krull, Kathleen (Houghton Mifflin Harcourt, 2014)
Profiles famous explorers in history and offers facts about each one. Features Leif Ericson, Marco Polo, Henry Hudson, Daniel Boone, Isabella Bird, Mary Kingsley, Matthew Henson, and Sally Ride among others.